Mandibular advancement splints for the treatment of obstructive sleep apnea. (2nd January 2020) - Chan, Andrew S. L.; Sutherland, Kate; Cistulli, Peter A.
ABSTRACT: Introduction : Obstructive sleep apnea (OSA) is a chronic condition which requires a comprehensive chronic disease management model, rather than a device-focused approach, so as to achieve the best possible health outcomes. Oral appliances are the main alternative to continuous positive airway pressure (CPAP) for the treatment of OSA. There has been an expansion of the research evidence to support the use of oral appliances in clinical practice and the clinical use of oral appliances for the treatment of OSA has become a mainstream practice. Areas covered : This review summarizes the evidence base for the use of oral appliances for the treatment of OSA. The types of oral appliances; their mechanism of action and clinical efficacy for the treatment of OSA; adverse effects, and the impact on patient acceptability and treatment adherence; and clinical effectiveness and health outcomes are discussed. Expert opinion : Personalization of treatment is vitally important in OSA and is a pre-requisite for optimizing adherence with treatment which, in turn, is a key determinant of clinical effectiveness. Treatment of OSA with mandibular advancement splints could provide an equivalent health benefit to CPAP despite not achieving a complete normalization of polysomnographic indices, mediated by differences in adherence profiles.